Sturgeon-derived peptide LLLE alleviates colitis via regulating gut microbiota and its metabolites - Jie Lin; Jiani Yang; Leqi Cui; Ravinder Nagpal; Prashant Singh; Gloria Salazar; Qinchun Rao; Ye Peng; Quancai Sun (Current Research in Food Science)
Inflammatory bowel disease (IBD), encompassing ulcerative colitis (UC) and Crohn's disease, entails chronic inflammation of the gastrointestinal tract. The pathogenesis of IBD implicates genetic factors, gut microbiome alterations, and immune dysregulation, contributing to its increasing global prevalence. The sturgeon-derived peptide, which exhibits promising anti-inflammatory effects, provides potential therapeutic insights for managing IBD symptoms. This study aims to elucidate the therapeutic mechanisms of novel sturgeon-derived peptide (LLLE, Leu-Leu-Leu-Glu) by investigating their effects on intestinal inflammation, gut microbiota composition, and fecal metabolites in a mouse model of IBD. LLLE administration alleviated weight loss and disease activity index (DAI) scores in dextran sulfate sodium salt (DSS)-induced colitis in mice. Histopathological examination showed LLLE pretreatment improved colon morphology and histopathological condition and decreased serum interleukin-6 (IL-6) levels. 16S rRNA sequencing indicated LLLE-modulation of gut microbiota, especially alleviated DSS-elevated Bacteroidetes. Fecal metabolomic analysis unveiled that LLLE restores critical metabolites such as indole-3-propionic acid, which is pivotal in anti-inflammatory responses. Altogether, sturgeon peptide exhibits considerable promise as a therapeutic agent for colitis, owing to its anti-inflammatory effects, modulation of gut microbiota, and restoration of essential fecal metabolites.